Development of the Fisheries Economic Sector in the Sula Islands Regency - Musdar Muhammad; Bahrun Talib; Muhdar Muba (LP2M IAIN Palopo, 2025)
This study aims to analyze the potential, competitive advantages, development prospects, and specialization of commodities in the capture fisheries sub-sector in the Sula Islands Regency. Method: This study uses a descriptive quantitative method by analyzing secondary data from the Sula Islands Regency and North Maluku Province Statistics Agency, as well as primary data obtained through interviews. The data analyzed covers the period 2018-2023. The analyses used include LQ, DLQ, Combined LQ and DLQ Analysis, IS, Shift-Share, and Klassen Typology. The results of the analysis show that skipjack tuna, tuna, and other fish are base commodities, meaning they are able to serve local needs and be exported outside the region. However, from a future prospects perspective (DLQ), only other fish are classified as potential commodities, while skipjack tuna and tuna are categorized as unpromising, indicating a slowdown in comparative growth rates.The combined analysis of LQ and DLQ places Other Fish in Type I (Basic, Prospective), while Skipjack and Tuna are in Type III (Basic, Not Prospective). In terms of specialization, only Other Fish and Skipjack have a high level of specialization for development. Shift-Share analysis shows that Skipjack, Tongkol, and Other Fish have competitiveness (positive Differential Shift), but Skipjack and Tuna experience slow proportional growth (negative Proportional Shift). Klassen's typology classifies Skipjack, Tongkol, and Tuna as Advanced and Fast-Growing Sectors (high contribution and high comparative growth), while Other Fish is classified as a Fast-Developing Sector (low contribution but high comparative growth